Ternary nanostructures of Cr2O3/graphene oxide/conducting polymers for supercapacitor application - Asen, Parvin; Shahrokhian, Saeed; zad, Azam Iraji (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2018)
In this work, nanostructured composites of Cr2O3-graphene oxide (Cr2O3/GO) with conducting polymers; polyaniline (PANI) and polypyrrole (PPy) with the shape of cauliflower were synthesized via s simple and low cost one-step chronoamperometry method. The structures and morphologies of the resulting ternary nanocomposites were characterized by using Fourier transform infrared spectroscopy, X-ray diffraction, field emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The electrochemical capacitive properties of the prepared nanocomposites were evaluated by using cycle voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. The as-synthesized Cr2O3/GO/PANI and Cr2O3/GO/PPy composites exhibit a highest specific capacitance of 525 and 495 F g−1 at 5 A g−1 in the three-electrode tests, respectively. Interestingly, Cr2O3/GO/PANI and Cr2O3/GO/PPy composites retain 84 and 80% of their initial capacitance values after 4000 charge-discharge cycles, suggesting good electrochemical stability of the nanocomposite electrodes. The assembled symmetric devices based on Cr2O3/GO/PANI and Cr2O3/GO/PPy composites show a high specific capacitance of 263 and 100 F g−1 at the current density of 5 A g−1, respectively. [Display omitted] •Cr2O3/GO/CPs is deposited on SS using a potentiostatic method.•Cr2O3/GO/PANI showed an excellent specific capacitance of 895 F g−1 at 5 A g−1.•Cr2O3/GO/PPy has a good specific capacitance of 695 F g−1 at 5 A g−1.•Cr2O3/GO/PANI shows highest power and energy density among the prepared composite electrodes.